The fate of the Farallon slab beneath Patagonia and its links to Cenozoic intraplate magmatism, marine transgressions and topographic uplift - Navarrete Granzotto, César Rodrigo; Gianni, Guido Martin; Massaferro, Gabriela Isabel; Butler, Kristina (Earth-Science Reviews)
The arrival and subsequent stagnation of the Farallon/Nazca slab at the mantle transition zone below southern South America triggered seemingly unrelated large-scale geological processes in the second half of the Cenozoic. During this period, three poorly understood regional events have characterized the more recent geological history of Patagonia: i) the development of intense intraplate magmatism, ii) two large-scale marine transgressions, and iii) abnormally accelerated topographic uplift. We propose a geodynamic model that connects the subducting slab mechanisms to these events based on seismic tomography, 2-D kinematic reconstructions, dynamic subsidence models and a detailed literature review. According to our kinematic reconstruction, after the Paleocene-Eocene opening of the Aluk (Phoenix)/Farallon slab window, the Farallon oceanic slab arrived to the mantle transition zone below Patagonia at ~36–32 Ma. This event caused the physical perturbation of this mantle layer, and dehydration melting of the uplifted portions by wadsleyite breakdown, triggering an intense Oligocene-middle Miocene intraplate magmatism significantly influenced by subduction-derived fluids. Simultaneously, due to increasing disturbance of the lower mantle during the Farallon slab penetration and stagnation in the mantle transition zone, a large subduction-induced mantle flow cell began to tilt the South American plate. Tilting drove the two large marine transgressions which inundated much of the southern Argentina and Chile. Finally, in the latest Miocene-Pleistocene, Farallon-Nazca slab break-off induced the decompression melting of the sub-slab asthenosphere, generating the most recent magmatic episode in the north-central Patagonia. This magmatism was partially contemporaneous with the Chile ridge (Nazca/Antarctic) slab window-related southern Patagonian igneous activity; and although both episodes show evidence of mantle metasomatic inheritance, the north-central magmatism shows higher Th/La and 87Sr/86Sr ratios, and lower εNd ...